Curcumin for the treatment of pituitary adenomas: the potential of a single agent for multifaceted therapeutic effects - Yan, Zisheng; Liang, Chen; Nian, Fujia; Peng, Gang; Li, Yuntao; Guan, Jingyu; Pan, Ruihan; Song, Gaochao (Frontiers in Endocrinology, 2025)
Pituitary adenomas (PAs), accounting for 10–15% of intracranial tumors, cause significant morbidity through endocrine dysfunction and mass effects. While current treatments (surgery, pharmacotherapy, radiation) face challenges such as drug resistance, recurrence, and metabolic complications, curcumin emerges as a promising multi-target agent for PA management. This review synthesizes evidence on curcumin’s dual roles: suppressing tumor progression and ameliorating hormone-driven metabolic disorders.Antitumor mechanismsCurcumin inhibits PA proliferation by modulating cell cycle proteins, inducing apoptosis via pro-apoptotic protein upregulation and anti-apoptotic suppression. It targets key pathways like NF-κB, reducing VEGF/HIF-1α-driven angiogenesis and MMP-9-mediated invasion. Synergistic effects enhance existing therapies: low-dose curcumin potentiates bromocriptine in prolactinomas by regulating ERK/EGR1 and AKT/GSK-3β, while in aggressive PAs, it may overcome temozolomide resistance by downregulating DNA repair enzymes.Metabolic regulationBeyond antitumor effects, curcumin mitigates hormone-induced metabolic dysregulation. It suppresses excess ACTH, GH, and prolactin secretion in functional PAs. For GH adenomas, curcumin improves insulin resistance by activating AMPK, enhancing skeletal muscle glucose uptake, and suppressing hepatic gluconeogenesis. It also reduces inflammatory cytokines and oxidative stress, protecting against cortisol-induced glycometabolic dysfunction and PRL/GH-mediated bone loss via RANKL/OPG pathway modulation.ConclusionCurcumin’s ability to concurrently target tumor growth, hormone hypersecretion, and metabolic complications positions it as a unique “one drug, multiple effects” candidate. Future research must prioritize PA-specific mechanistic studies and advanced delivery systems to realize its clinical potential.